New cosmogenic nuclide constraints on Late Glacial and Holocene glacier fluctuations in the sub-Antarctic Indian Ocean (Kerguelen Islands, 49°S). (1st May 2022) - Charton, Joanna; Schimmelpfennig, Irene; Jomelli, Vincent; Delpech, Guillaume; Blard, Pierre-Henri; Braucher, Régis; Verfaillie, Deborah; Favier, Vincent; Rinterknecht, Vincent; Goosse, Hugues; Crosta, Xavier; Chassiot, Léo; et al.
Abstract: Cosmogenic nuclide dating of glacial landforms on the Kerguelen Archipelago (49°S, 69°E) gives the opportunity to study multi-millennial glacier fluctuations within the sub-Antarctic sector of the Indian Ocean. We here dated such geomorphic features to provide time constraints over the last 17, 000 years using in situ -produced 36 Cl in three glacial valleys: Val Travers valley, Ampere Glacier valley and Arago Glacier valley. For the first time, a combination of in situ- produced 36 Cl and 10 Be dating and 26 Al/ 10 Be ratios analysis was performed in the quartz-bearing syenite boulders of the Arago Glacier site. In addition, a Bayesian approach was computed to obtain a better constraint on moraine dating. Glacial advances occurred during the Late Glacial at 16.0 ± 1.9 ka and at 12.9 ± 1.7 ka in Val Travers, and at 13.6 ± 1.8 ka in Arago Glacier valley, probably linked to the Heinrich Stadial 1 and/or Antarctic Cold Reversal events, respectively. This suggests that all glaciers at this latitude were broadly sensitive to the large-scale climatic signal of the Antarctic Cold Reversal. So far, no Early nor Mid-Holocene moraines have been found in the glacial valleys on Kerguelen, indicating that the glaciers had probably receded significantly during these periods. This is in agreement with previously determined 14 C ages from peat bogs, which suggest extensive deglaciation during several millennia of the Holocene period. Samples from glacially-polished bedrock surfaces (ranging from ∼4.4 ka to ∼14 ka) at Ampere Glacier site also suggest that this valley was ice free for several millennia during the Holocene. Finally, glaciers seem to have re-advanced only during the Late Holocene, especially within the last millennium, at ∼1 ka, ∼ 430 yr and ∼300 yr. A comparison of this new dataset with the available 10 Be ages from other southern mid-latitude regions during the Holocene allows the identification of three different glacier evolution patterns. We suspect that variations of Kerguelen glaciers, which are located in the Southern Indian Ocean, were controlled by the combined effects of sea surface temperature related to the variations of the Antarctic Polar Front and fluctuations of precipitation related to long-term variations of the Southern Annular Mode. Highlights: First 36 Cl, 10 Be and 26 Al dating in quartz-bearing syenites. Evidence of Heinrich Stadial 1 and Antarctic Cold Reversal advances is provided. Holocene maximal glacier extent occurred during the Late Holocene. Non-homogeneous glacier evolution during the Holocene in sub-Antarctic region. Kerguelen Holocene glaciers' behaviour differs from other sub-Antarctic regions.